Mutation-driven parallel evolution in emergence of ACE2-utilizing sarbecoviruses - Gao, Bin; Zhu, Shunyi (Frontiers in Microbiology, 2023)
Mutation and recombination are two major genetic mechanisms that drive the evolution of viruses. They both exert an interplay during virus evolution, in which mutations provide a first ancestral source of genetic diversity for subsequent recombination. Sarbecoviruses are a group of evolutionarily related β-coronaviruses including human severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2 and a trove of related animal viruses called SARS-like CoVs (SL-CoVs). This group of members either use or not use angiotensin-converting enzyme 2 (ACE2) as their entry receptor, which has been linked to the properties of their spike protein receptor binding domains (RBDs). This raises an outstanding question regarding how ACE2 binding originated within sarbecoviruses. Using a combination of analyses of phylogenies, ancestral sequences, structures, functions and molecular dynamics, we provide evidence in favor of an evolutionary scenario, in which three distinct ancestral RBDs independently developed the ACE2 binding trait via parallel amino acid mutations. In this process, evolutionary intermediate RBDs might be firstly formed through loop extensions to offer key functional residues accompanying point mutations to remove energetically unfavorable interactions and to change the dynamics of the functional loops, all required for ACE2 binding. Subsequent optimization in the context of evolutionary intermediates led to the independent emergence of ACE2-binding RBDs in the SARS-CoV and SARS-CoV-2 clades of Asian origin and the clade comprising SL-CoVs of European and African descent. Our findings will help enhance our understanding of mutation-driven evolution of sarbecoviruses in their early history.